2012
DOI: 10.1007/s10853-012-6591-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative microscopic and spectroscopic analysis of temperature-dependent growth of WO3 and W0.95Ti0.05O3 thin films

Abstract: We present a comparative microscopic and spectroscopic study of the morphology and composition of WO 3 and W 0.95 Ti 0.05 O 3 thin films, grown by radio-frequency magnetron reactive sputtering at substrate temperatures varied from room temperature to 500°C, using atomic force microscopy (AFM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). With increasing growth temperature, the AFM results show increase in the average crystallite size and in the surface roughness for both undoped and doped sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
4
17
0
1
Order By: Relevance
“…The Ti was found to promote stability both for crystallization at elevated temperature and for the electrochromic performance under extended cycling in a Li-conducting electrolyte. Our data are consistent with those in prior work [14][15][16][17][18]26,30] as regards crystallization and support earlier evidence concerning the ability of Ti to prevent permanent incorporation of Li. Furthermore, our data indicate that low sputtering powers are connected with improved stability under electrochemical cycling.…”
Section: Remarks and Conclusionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Ti was found to promote stability both for crystallization at elevated temperature and for the electrochromic performance under extended cycling in a Li-conducting electrolyte. Our data are consistent with those in prior work [14][15][16][17][18]26,30] as regards crystallization and support earlier evidence concerning the ability of Ti to prevent permanent incorporation of Li. Furthermore, our data indicate that low sputtering powers are connected with improved stability under electrochemical cycling.…”
Section: Remarks and Conclusionsupporting
confidence: 93%
“…Other, supporting studies on the electrochromism in W-Ti oxide have been reported for films prepared by sputtering [16][17][18][19], chemical technology involving spraying [20][21][22] dipping [16,23] or spinning [24][25][26], electrodeposition [27,28] and anodization [29]. The enhanced stability has been investigated in depth in recent work on W-Ti oxide films made by sputtering [30,31] and chemical techniques [26]. Data based on electrochemical measurements, transmission electron microscopy, atomic force microscopy and Raman spectroscopy verify [26,30] that the Ti addition makes the crystallization occur at a higher temperature than in a film of pure W oxide.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…can be boosted by incorporating some titanium [16][17][18][19][20][21] which prevents crystallization that otherwise may degrade the WO 3 [21][22][23]. Here we combine these beneficial effects and present data from a comprehensive study of W 1-x-y Ni x Ti y O 3 thin films.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Analyses also showed that the W atoms were in the formal valence band +6, [78] with the observed binding energy peaks at around 35.8 and 37.8 eV being associated with spin-orbit splitting of the W 4f7/2 and W 4f5/2 respectively (Figure 3c). [88] Lastly, in the O core level XPS spectrum (Figure 3d), the 530.8 eV peak corresponding to the O1s [89] showed no changes in all the samples being investigated, thus indicating that Pt coating and r-GO modification, while changing the surface chemical/physical properties of the hybrids did not affect their crystalline structure.…”
Section: Resultsmentioning
confidence: 93%